Epidemiological shifts in chronic kidney disease: a 30-year global and regional assessment - Kaili Qin; Jianbo Qing; Qian Wang; Yafeng Li (BMC Public Health)
Abstract Background Chronic kidney disease (CKD) presents a growing global health challenge, with significant variability in disease burden across different regions and countries. This study aimed to analyze the trends in incidence, prevalence, mortality, and disability-adjusted life years (DALYs) for CKD from 1990 to 2019, utilizing data from the Global Burden of Disease Study. Methods We conducted an in-depth study on the global and age-standardized incidence, prevalence, mortality, and DALYs of CKD, and assessed trends over a 30-year period. Additionally, we explored the associations between healthcare access and quality (HAQ), the Socio-Demographic Index (SDI), and CKD. Furthermore, we conducted a detailed analysis of six risk factors closely related to CKD, and based on these findings, provided strong evidence for enhancing the management of CKD. Results In 2019, there were 18,986,903 cases of CKD, with an average annual percent change (AAPC) of 1.82 (95% CI = 1.8 to 1.82) in incidence since 1990. The age-standardized incidence rate increased from 192.45 per 100,000 in 1990 to 233.65 per 100,000 in 2019. Prevalence also rose, with a total of 69,729,430 cases in 2019 and an AAPC of 1.19 (95% CI = 1.19 to 1.2). Mortality and DALYs have increased correspondingly, with the mortality rate reaching 18.29 per 100,000 and total DALYs at 41,538,592 in 2019. The analysis showed that higher HAQ levels are associated with better outcomes in terms of lower mortality and DALY rates, whereas lower HAQ levels correlate with poorer outcomes. In addition, high fasting plasma glucose and high systolic blood pressure are the main contributors to CKD-related deaths, with their population attributable fraction (PAF) significantly decreasing as the SDI decreases. Conclusion The burden of CKD has significantly increased over the past three decades, influenced by demographic changes and variations in healthcare quality and access. Effective public health strategies and improvements in healthcare delivery are needed to address the disparities in CKD outcomes globally.